Bayle--political writings - Bayle, Pierre, 1647-1706 (Cambridge texts in the history of political thought., 2000)
Sally Jenkinson's masterful new selection from Bayle's Dictionnaire Historique et Critique presents the reader with a coherent path through Bayle's vast work. Her authoritative translation, careful text selection, and lucid introduction will be welcomed by scholars and students of the history of ideas, political theory, cultural history and French studies.